Surface Modification of Silica Particles Taken from Waste Glass by Surfactant Treatment for Light Scattering Application - Kanokthip Boonyarattanakalin; Wanichaya Mekprasart; Aphisit Manivong; Tirapat Wechprasit; Krisana Chongsri; Wisanu Pecharapa (My University, 2022)
T his work aims to modify the surface of silicon dioxide particles for high dispersion property in the host matrix. Silicon dioxide powders were obtained from wasted material as broken beaker glass and reduced its particle size by high energy milling process operating at 500 rpm for 30 min. These particles can be proposed as an effective light scatterer and applied in the transparent light planar waveguide for the improvement of light emission performance. However, the main problem of using milled silica powder is the poor dispersion in the polymer matrix. Therefore, the surface modification method is a key role to resolve this obstacle by using polymer surfactant agents as polyvinyl alcohol, polyethylene glycol, and sodium hexametaphosphate. The proper polymer surfactant in the surface modification on silica powders has been revealed. The particle size of each condition was analyzed by a particle analyzer. Modified silica particle size with polymer surfactants trended to decrease lower than 1 μm owing to good dispersion of the particles by polymer chain and interaction between silica and surfactant surface. Chemical functional groups on modified silica powders were investigated by Fourier transform-infrared (FT-IR) spectroscopy. FTIR spectra shown that main chemical components of all samples were composed of silica and borate chemical bonding. Meanwhile, the O-H stretching vibration appeared in the spectra was a key role for particle size and good dispersion of modified surface silica particles in the solution. Moreover, light scattering property and transmission of modified silica with polymer surfactants in dispersion solution were detected by luminance meter and UV-Vis spectrometer to confirm its possibility for application in light scattering material. The best polymer surface for milled silica surface modification in this work was obtained from polyvinyl alcohol, which proved that the adjustment of surface charge and physical properties on the silica surface.
Keywords: Surface Modification; Particle (ecology); Advanced Fiber Optic Sensors